Women's Healthcare Providers' Range of Services and Collaborative Care. Issue 2 (22nd August 2012) - Farrow, Victoria A.; Lawrence, Hal; Schulkin, Jay
Abstract Physician shortages and healthcare reform are important topics in the healthcare field today. The utilization of the skills and professional competencies of nonphysician healthcare providers, as well as collaboration between physicians and nonphysician healthcare providers may in part provide a solution to some current healthcare concerns. The purposes of this study were to describe the range of services provided by nonphysician women's healthcare providers (WHCPs), and to begin to explore the collaborative relationship between obstetrician‐gynecologists (ob‐gyns) and WHCPs. Questionnaires were sent to ob‐gyns, certified nurse‐midwives, certified midwives, nurse practitioners (NPs), and physician's assistants (PAs) with questions regarding the types of services WHCPs provide, as well as collaboration between ob‐gyns and WHCPs. Overall, 62.1% of ob‐gyns employ WHCPs. NPs are the most common type of WHCP employed in our sample. WHCPs are more likely to be younger than ob‐gyns, and an overwhelming majority of WHCPs in our sample are female. Most reported that they are anticipating an expansion in the roles and services they provide over the next 5 years. In an era of healthcare reform, WHCPs may in part provide a solution to the growing physician shortage. Collaboration between ob‐gyns and WHCPs is a key aspect of the changing healthcare environment.